Detergent Insoluble Proteins and Inclusion Body-Like Structures Immunoreactive for PRKDC/DNA-PK/DNA-PKcs, FTL, NNT, and AIFM1 in the Amygdala of Cognitively Impaired Elderly Persons. Issue 1 (24th November 2017) - Gal, Jozsef; Chen, Jing; Katsumata, Yuriko; Fardo, David W; Wang, Wang-Xia; Artiushin, Sergey; Price, Douglas; Anderson, Sonya; Patel, Ela; Zhu, Haining; Nelson, Peter T
Abstract: Misfolded protein in the amygdala is a neuropathologic feature of Alzheimer disease and many other neurodegenerative disorders. We examined extracts from human amygdala (snap-frozen at autopsy) to investigate whether novel and as yet uncharacterized misfolded proteins would be detectable. Polypeptides from the detergent-insoluble, urea-soluble protein fractions of amygdala were interrogated using liquid chromatography-electrospray ionization-tandem mass spectrometry. Among the detergent-insoluble proteins identified in amygdala of demented subjects but not controls were Tau, TDP-43, Aβ, α-synuclein, and ApoE. Additional detergent-insoluble proteins from demented subjects in the high-molecular weight portion of SDS gels included NNT, TNIK, PRKDC (DNA-PK, or DNA-PKcs), ferritin light chain (FTL), AIFM1, SYT11, STX1B, EAA1, COL25A1, M4K4, CLH1, SQSTM, SYNJ1, C3, and C4. In follow-up immunohistochemical experiments, NNT, TNIK, PRKDC, AIFM1, and FTL were observed in inclusion body-like structures in cognitively impaired subjects' amygdalae. Double-label immunofluorescence revealed that FTL and phospho-PRKDC immunoreactivity colocalized partially with TDP-43 and/or Tau inclusion bodies. Western blots showed high-molecular weight "smears", particularly for NNT and PRKDC. A preliminary genetic association study indicated that rare NNT, TNIK, and PRKDC gene variants had nominally significant association with Alzheimer-type dementia risk. In summary, novel detergent-insoluble proteins, with evidence of proteinaceous deposits, were found in amygdalae of elderly, cognitively impaired subjects.